The Mediating Effect of Organizational Culture and Work Fatigue on Work Life Balance in the Context of Work from Home among Indonesian Workers - Hongdiyanto, Charly; Halcon, Frederick Abainza; Yusup, Adi Kurniawan; Ongkowijoyo, Gracia (Bina Nusantara University, 2025)
Remote work has existed for quite some time, but has gained popularity with the onset of the COVID-19 pandemic, as all activities had to be conducted from home. The research gap lies in the scarcity of empirical evidence on how organizational culture and work fatigue mediate the relationship between Work From Home (WFH) and work-life balance (WLB), especially in the Indonesian context. This study examined whether organizational culture and work fatigue mediate the impact of WFH on WLB among Indonesian workers. The research aimed to understand how work-life balance is affected by organizational culture and work fatigue among Indonesian remote workers. Using purposive sampling, the research gathered data from 112 respondents and analyzed them with Smart PLS. The findings indicate that the direct relationship between WFH and WLB, as well as work fatigue is not significant. Similarly, the mediating effect of organizational culture and work fatigue on the relationship between work-from-home and work-life balance were not significant. Furthermore, the link between organizational culture and work-life balance is not significant. A significant relationship is observed only between work fatigue and WLB, and between WFH and organizational culture. This research is crucial because while remote work offers flexibility, it also poses challenges such as fatigue and blurred boundaries that may jeopardize employees' well-being. Understanding these dynamics helps organizations in developing supportive cultures and strategies to enhance employee WLB in the post-pandemic digital-first era.